PD-1 Expression on Mycobacterium tuberculosis-Specific CD4 T Cells Is Associated With Bacterial Load in Human Tuberculosis - Day, Cheryl L.; Abrahams, Deborah A.; Bunjun, Rubina; Stone, Lynnett; de Kock, Marwou; Walzl, Gerhard; Wilkinson, Robert J.; Burgers, Wendy A.; Hanekom, Willem A. (Frontiers in Immunology, 2018)
Persistent antigen stimulation in chronic infections has been associated with antigen-specific T cell dysfunction and upregulation of inhibitory receptors, including programmed cell death protein 1 (PD-1). Pulmonary tuberculosis (TB) disease is characterized by high levels of Mycobacterium tuberculosis (Mtb), yet the relationship between bacterial load, PD-1 expression, and Mtb-specific T cell function in human TB has not been well-defined. Using peripheral blood samples from adults with LTBI and with pulmonary TB disease, we tested the hypothesis that PD-1 expression is associated with bacterial load and functional capacity of Mtb-specific T cell responses. We found that PD-1 was expressed at significantly higher levels on Th1 cytokine-producing Mtb-specific CD4 T cells from patients with smear-positive TB, compared with smear-negative TB and LTBI, which decreased after completion of anti-TB treatment. By contrast, expression of PD-1 on Mtb-specific CD8 T cells was significantly lower than on Mtb-specific CD4 T cells and did not differ by Mtb infection and disease status. In vitro stimulation of PBMC with Mtb antigens demonstrated that PD-1 is induced on proliferating Mtb-specific CD4 T cells and that Th1 cytokine production capacity is preferentially maintained within PD-1+ proliferating CD4 T cells, compared with proliferating Mtb-specific CD4 T cells that lack PD-1 expression. Together, these data indicate that expression of PD-1 on Mtb-specific CD4 T cells is indicative of mycobacterial antigen exposure and identifies a population of effector cells with Th1 cytokine production capacity. These studies provide novel insights into the role of the PD-1 pathway in regulating CD4 and CD8 T cell responses in Mtb infection and provide rationale for future studies to evaluate PD-1 expression on antigen-specific CD4 T cells as a potential biomarker for bacterial load and treatment response in human TB.